Analisis Implementasi Laporan Keuangan BUMDES Sesuai SAK EMKM: Studi Kasus BUMDES Gemilang Desa Molowahu - Abdullah, Anggriliani; Monoarfa, Rio; Pratiwi Husain, Siti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The results of this research show that the presentation of financial reports for Bumdes Gemilang Molowahu does not apply SAK EMKM. By presenting fairly, compliance with SAK EMKM, business continuity by making an assessment of the entity's capabilities, consistent presentation, and complete financial reports, namely: Simple Cash Flow Balance Sheet. The financial report of Bumdes Gemilang Molowahu has not fully implemented SAK EMKM, because there are components that are not presented, namely the final notes to the financial report, therefore, the Bumdes financial report is incomplete and does not comply with the provisions of SAK EMKM. In the balance sheet financial report, there are items that are not presented, namely intangible assets, tax liabilities and determined liabilities. Profit and loss contains missing items, namely tax expense and net profit or loss